Relationship between Substance use and Endocrine Disorders: A Narrative Review - Sharma, Pawan; Balhara, Yatan Pal Singh (Journal of Psychiatrists’ Association of Nepal, 2022)
Substance use disorder is one of the significant public health concerns and the co-morbidity with endocrine disorders has a potential to cause adverse outcomes. There is a definite link between substance use and dysregulation of endocrine system at a level of causation, association, management and drug interaction. It has been seen that the screening of substance use while managing endocrine disorders is a must. Also, integrated management of both of these chronic condition with collaborative care approach can not only help in effective management but also improve the outcomes in terms of mortality, cost effectiveness, stigma and financial burden. Though considered important this common area seems to be understudied. Hence we recommend that this co-occurrence of substance use and endocrine disorders should be studied and guidelines be developed for the effective management.